2013
DOI: 10.1371/journal.pone.0074566
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchical Process of Differentiation of Long-Lived Antibody-Secreting Cells Is Dependent on Integrated Signals Derived from Antigen and IL-17A

Abstract: Switched CD19-positive memory B cells purified from mice with chronic immune response against Thalassophryne nattereri venom proteins were cultured with venom or cytokines. Our results confirm the existence of a hierarchic process of differentiation: activated memory B cells progressively acquire increasing levels of CD138 and decreasing levels of CD45R/B220 to finally arrive at ASC with B220neg phenotype, which are IgG1-secreting cells. Only Bmem from peritoneal cavity or bone marrow of VTn immunized mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Then, we confirmed in an in vitro model the existence of a hierarchical process in which CD19-positive Bmem become CD138-positive IgG producing-ASC by a mechanism directly dependent on B-cell receptor (BCR) stimulation by venom, which could be potentiated by IL-17A [30]. Collectively, these studies shed new light on survival factors involved in the differentiation and maintenance of ASC in inflamed tissue and demonstrated that these cells require signals derived from antigen and IL-17A for the secretion of venom-specific antibodies for long periods of time.…”
Section: Reviewmentioning
confidence: 77%
“…Then, we confirmed in an in vitro model the existence of a hierarchical process in which CD19-positive Bmem become CD138-positive IgG producing-ASC by a mechanism directly dependent on B-cell receptor (BCR) stimulation by venom, which could be potentiated by IL-17A [30]. Collectively, these studies shed new light on survival factors involved in the differentiation and maintenance of ASC in inflamed tissue and demonstrated that these cells require signals derived from antigen and IL-17A for the secretion of venom-specific antibodies for long periods of time.…”
Section: Reviewmentioning
confidence: 77%
“…Long-term immune protection requires the persistence of vaccine antibodies and/or the generation of immune memory cells capable of rapid and effective re-activation upon subsequent exposure. Data from work on T. nattereri venom in mice strongly implies that IL-17A derived from effector memory T-cells govern the differentiation of germinal center derived-memory-B cells into antibody-secreting cells and maintain their longevity through a mechanism directly dependent on B-cell receptors, and T. nattereri venom was found to affect these processes [ 123 , 124 , 125 ]. Additionally, it was found that the proteolytic activity of a novel toxin family from T. nattereri venom, known as Natterins, is critical for the hierarchical differentiation of antibody-secreting cells, and for the adjuvanticity of the venom [ 126 , 127 ].…”
Section: Venom Activitiesmentioning
confidence: 99%
“…This may indicate that the participation of TLR4 in GC responses alters the nature of output from GC B cells to LLPCs as the response progresses. We examined the IL‐17A secretion in serum after immunization, because IL‐17A can assist with the survival of LLPCs . However, we did not observe a significant difference between immunized WT and TLR4‐KO mice.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, several factors contribute to the survival of LLPCs, such as IL‐17A . To test whether the level of IL‐17A was affected by the TLR4 deficiency, we measured the secretion of IL‐17A using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%